Diversitas Species Tumbuhan Paku Hias dalam Upaya Melestarikan Sumberdaya Hayati Kebun Raya Baturraden - Sukarsa Sukarsa; Hexa Apriliana Hidayah; Titi Chasanah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
Baturraden Botanical Garden is a complex ecosystem. Its natural resources, including several species of fern, provide an opportunity to be managed sustainably so it can be used to fulfill a long term of public need. This research was aimed to know the diversity of fern species and its potential as ornamental plants. The research was using survey method. The data was analyzed using descriptive comparative analysis. Species identification was performed by comparing the samples with herbarium specimens and also using identification keys. During the observation, 26 species of fern were found, which is consisted of 14 terrestrial species and 12 epiphyte species. Nephrolepis bisserata (Sw.) Schott. was terrestrial species with highest individual number and widest dispersion, whereas terrestrial species with smallest individual number and the narrowest distribution was Blechnum orientale Linn. Epiphytic fern species with highest individual number and widest dispersion was Nephrolepis falcata (Cap.) C. Chr., whereas epiphytic species with smallest individual number and narrowest distribution was Davallia triphylla Hk. From 26 fern species which were found at Baturraden Botanical Garden, 22 fern species were potential as ornamental plant which can be grew up either on land, pot or on host plant.